Two Symbolic Forms of Mental Capacity in Psychoanalysis - Chuansong HUO; Dongcheng CHI (Yixue yu zhexue, 2025)
In psychoanalysis, symbols have a crucial rhetorical and pathological significance. Through discussing and exploring Freudian and Kleinian theories of symbols, the research finds that in Freud's theory, the symbol is a regressive activity of the mind, while in Klein's theory, it is a developmental, progressive one. These discoveries prove that the symbolic capacity, as a specific mental capacity of human beings, holds two different forms. On one hand, analysands consciously use rhetorical symbols to express their emotions and the content of their experiences; on the other hand, they also unconsciously use symbols in their dreams and discourses. The distinction between these two forms of symbolization offers a unique framework for understanding both clinical practice and the workings of the human mind.